Comparative Analysis of Triglycerides From Different Regions and Mature Lactation Periods in Chinese Human Milk Project (CHMP) Study - Zhu, Huiquan; Liang, Aimei; Wang, Xiaodan; Zhang, Wenyuan; Zhang, Yumeng; He, Xiangyu; Liu, Ying; Jiang, Shilong; Lu, Jing; Lv, Jiaping (Frontiers in Nutrition, 2021)
The types and contents of triglycerides in mature milk of different regions and lactation periods have great significance to improve the quality of infant formula. In this research, the 201 mature milk samples which from eight different Chinese cities (Chengdu, Weihai, Lanzhou, Jinhua, Beijing, Guangzhou, Zhengzhou and Harbin) and six sequential lactation time (30, 60, 90, 120, 150, and 180 days) were selected to detect the triglycerides. The result was demonstrated that 66 triglycerides were detected, which ACN number was located in the scope of 34-54, and DB number 0 to 6. The OPO, OPL, and OOO are three abundant of triglycerides in mature human milk, and the relative content of them all are more than 4 % in all lactation areas and times, and the content of U2S and LLL triglycerides were richest in mature milk. In addition, it was also found that regions have a greater impact on the content of triglycerides in human milk compared with lactation time, and Guangzhou has a significant difference from other regions among them. These will provide the more comprehensive theoretical basis for the production of infant formula milk powder in China.